VALIDASI BAKTERI PELARUT FOSFAT INDIGENUS MADURA PADA RHIZOSFER - Gita Pawana (Agrovigor, 2014)
ABSTRACTOften generalized that the determination effectiveness of biological agents depends on environment. The purpose of this study is to obtain an explanation of the role of growth limiting factors, chemical or physical on the effectiveness Madura indigenous Pseudomonas aeruginosa as a phosphate solubilizing. The method used in achieving the goal of research is, perform in vitro studies on the type of carbon source (sugar) and the level of salinity as the growth limiting factors of bacteria on the effectiveness of phosphate dissolution and study the influence of the the rice rhizosphere type of phosphate available. Found that in vitro, the type of carbon source and salinity levels affect phosphate concentrations and abundance of bacterial cells. Increased levels of salinity decreases the abundance of bacterial cells. Average cell population fluorescent pseudomonads in fields rice rhizosphere is higher than the lowland rice rhizosphere, the cell population fluorescent pseudomonads higher level provide higher available phosphate and vegetative growth of rice better.Key words:  Phosphate solubilizing, limiting growth, carbon source, salinity, the rhizosphere Madura indigenous.